Understanding the business model design for complex technology systems: The case of the bioeconomy - Stefanie Bröring; Vanessa Thybussek (EFB Bioeconomy Journal, 2023)
The commercialization of bio-based technologies can foster the transition from a fossil-based to a bio-based industry. However, the development of bio-based technologies often implies a co-evolution of process and product technologies (compare for example a biorefinery producing biobased specialty chemicals) as well as the design of a larger systems architecture involving different actors. Additionally, technologies are increasingly developed in a modular design, where different components of the final technology are managed by several actors that only together engage in value-creation. Complexity of the system complicates the design of a business model due to different interdependencies and the need for co-evolution of different components of a larger technology system. To alleviate these challenges, we aim to build a framework that disentangles the interdependencies of technologies and actors as well as the inherent complexity of technology systems and guides the design of a business model for a complex technology system. By drawing upon five well-established concepts, namely (i) the technology-product-market linkages, (ii) the technology system, (iii) the system-of-systems perspective, (iv) the technology innovation system and (v) the ecosystem pie model, the proposed framework supports the design of a business model for scientist entrepreneurs of a focal technology, which aligns well with the overall (eco)system. To illustrate its use, we apply our proposed framework to the bioeconomic case of microbial palm oil produced in a biorefinery.